2018
DOI: 10.1038/s41426-018-0132-z
|View full text |Cite
|
Sign up to set email alerts
|

Zika convalescent macaques display delayed induction of anamnestic cross-neutralizing antibody responses after dengue infection

Abstract: Structural similarities between Zika (ZIKV) and dengue virus (DENV) leads to the induction of cross-reactive responses. We have previously demonstrated that ZIKV exposed macaques significantly enhance DENV viremia. Here we show that this enhancement of DENV infection occurred in the presence of high levels of DENV cross-reactive IgG1 subclass of binding antibodies (bAb) with low DENV neutralizing antibody (nAb) activity (<1:10). The DENV-2 nAb titres after ZIKV infection were, however, higher than those induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
(33 reference statements)
0
21
1
Order By: Relevance
“…Further characterization of ZIKV early convalescent sera from these macaques indicated that there is a delayed induction of the cross-reactive Ab response against DENV, supporting no cross-protection against the outcome of DENV infection 39 . Despite these findings, further studies are needed to dissect the complementary role of the innate, humoral and cellular immune response to mechanistically explain these findings.…”
Section: Introductionmentioning
confidence: 92%
“…Further characterization of ZIKV early convalescent sera from these macaques indicated that there is a delayed induction of the cross-reactive Ab response against DENV, supporting no cross-protection against the outcome of DENV infection 39 . Despite these findings, further studies are needed to dissect the complementary role of the innate, humoral and cellular immune response to mechanistically explain these findings.…”
Section: Introductionmentioning
confidence: 92%
“…Other groups also have found no evidence of enhancement of ZIKV pathogenesis in DENV-immune macaques 194,195 . However, in a study in rhesus macaques, prior exposure to ZIKV resulted in enhanced DENV peak viraemia 196 , and this was associated with delayed induction of memory cross-neutralizing antibody responses 197 . This observation may have implications for ZIKV vaccine development in areas endemic for DENV infections.…”
Section: Emerging and Re-emerging Threatsmentioning
confidence: 99%
“…On the other hand, observations from arbovirus surveillance in Brazil suggest a decrease in DENV circulation after the ZIKV outbreak, possibly due to DENV cross-neutralization by ZIKV antibodies [80]. Additionally, there are indications that these cross-neutralizing ZIKV antibodies can prevent DENV ADE [81, 82]. However, for DENV, it is demonstrated that the risk of severe disease depends on the titer of preexisting DENV antibodies [16].…”
Section: Enhancement Of Denv By Zikv Antibodiesmentioning
confidence: 99%
“…However, for DENV, it is demonstrated that the risk of severe disease depends on the titer of preexisting DENV antibodies [16]. Therefore, it is plausible that cross-neutralizing ZIKV antibodies can prevent DENV ADE, whereas cross-reactive, binding ZIKV antibodies can enhance DENV infection, stressing the importance of measuring the balance between neutralizing and nonneutralizing antibodies in studies on pathogenesis [81]. The possibility of DENV ADE by ZIKV antibodies is especially of importance in DENV-naïve persons who live in DENV-endemic areas and who have had a previous ZIKV infection.…”
Section: Enhancement Of Denv By Zikv Antibodiesmentioning
confidence: 99%